Political party in Islamic Republic of Iran: A review. - Asayesh, Hossein; Abd. Halim, Adlina; Jawan, Jayum; Shojaei, Seyedeh Nosrat (Canadian Center of Science and Education (CCSE), 2011)
The political party is a means of connecting the political process with society and it helps to improve the political system. This paper looks at the history of political parties in Iran after the Islamic Revolution, and also considers the two main official political party groups: the Right Party and the Left Party. The article describes how each party shapes its views and develops its programs, and finally examines their similarities and differences in the field of economics, politics and culture.